Correlation Analysis Between Trace Elements and Colorectal Cancer Metabolism by Integrated Serum Proteome and Metabolome - Zheng, Zhi; Wei, Qingfeng; Wan, Xianghui; Zhong, Xiaoming; Liu, Lijuan; Zeng, Jiquan; Mao, Lihua; Han, Xiaojian; Tou, Fangfang; Rao, Jun (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is currently the third most common cancer with a high mortality rate. The underlying molecular mechanism of CRC, especially advanced CRC, remains poorly understood, resulting in few available therapeutic plans. To expand our knowledge of the molecular characteristics of advanced CRC and explore possible new therapeutic strategies, we herein conducted integrated proteomics and metabolomics analyses of 40 serum samples collected from 20 advanced CRC patients before and after treatment. The mass spectrometry-based proteomics analysis was performed under data-independent acquisition (DIA), and the metabolomics analysis was performed by ultra-performance liquid chromatography coupled with time-of-flight tandem mass spectrometry (UPLC-TOF-MS/MS). Trace elements including Mg, Zn, and Fe were measured by inductively coupled plasma spectrometry (ICP-MS) analysis. Four of the 20 patients had progressive disease (PD) after treatment, and clinical test results indicated that they all had impaired liver functions. In the proteomics analysis, 64 proteins were discovered to be significantly altered after treatment. These proteins were enriched in cancer-related pathways and pathways participating immune responses, such as MAPK signaling pathway and complement/coagulation cascades. In the metabolomics analysis, 128 metabolites were found to be significantly changed after treatment, and most of them are enriched in pathways associated with lipid metabolism. The cholesterol metabolism pathway was significantly enriched in both the proteomics and metabolomics pathway enrichment analyses. The concentrations of Mg in the serums of CRC patients were significantly lower than those in healthy individuals, which returned to the normal range after treatment. Correlation analysis linked key lipids, proteins, and Mg as immune modulators in the development of advanced CRC. The results of this study not only extended our knowledge on the molecular basis of advanced CRC but also provided potential novel therapeutic targets for CRC treatment.